Selection of biophysically favorable antibody variants using a modified Flp-In CHO mammalian display platform - Huhtinen, Olli; Salbo, Rune; Lamminmäki, Urpo; Prince, Stuart (Frontiers in Bioengineering and Biotechnology, 2023)
Mammalian display enables the selection of biophysically favorable antibodies from a large IgG antibody library displayed on the plasma membrane of mammalian cells. We constructed and validated a novel mammalian display platform utilizing the commercially available Flp-In CHO cell line as a starting point. We introduced a single copy of a landing pad for Bxb1 integrase-driven recombinase-mediated cassette exchange into the FRT site of the Flp-In CHO line to facilitate the efficient single-copy integration of an antibody display cassette into the genome of the cell line. We then proceeded to demonstrate the ability of our platform to select biophysically favorable antibodies from a library of 1 x 106 displayed antibodies designed to improve the biophysical properties of bococizumab via randomization of problematic hydrophobic surface residues of the antibody. Enrichment of bococizumab variants via fluorescence-activated cell sorting selections was followed by next generation sequencing and thorough characterization of biophysical properties of 10 bococizumab variants that subsequently allowed attribution of the mutations to the biophysical properties of the antibody variants. The mammalian displayed variants exhibited reduced aggregation propensity and polyreactivity, while critically retaining its target binding thereby demonstrating the utility of this valuable tool.